A research annual - Samuels, Warren J.; Biddle, Jeff E. (Research in the history of economic thought and methodology ;, 2000)
This volume examines topics in the discourse and methodology of economics, focusing on the types of metaphor, the use of mathematics, and the Economics of ... literature. Other articles deal with some continuities between Adam Smith and Max Weber, and pre-Keynesian heterodoxy in macro-monetary dynamics. A special section presents multiple reviews of books by Yuval Yonay and Perry Mehrling on American economic thought during the inter-war period. Also included are reviews covering topics such as Classical political economy, Marx, communitarianism, Scholasticism, Hume's political ideas, and rational expectations.